Effects of an oral-pharyngeal motor training programme on children with obstructive sleep apnea syndrome in Hong Kong: A retrospective pilot study - S.Y. Cheng; S.H.W. Kwong; W.M. Pang; L.Y. Wan (SAGE Publishing, 2017)
Background: This study aimed to investigate the effects of an oropharyngeal motor training programme on children with Obstructive Sleep Apnea Syndrome (OSAS) in Hong Kong. Methods: In this retrospective study, we reviewed the outcomes of 10 children with OSAS who had received an oropharyngeal motor training programme in Occupational Therapy Department of an acute hospital in Hong Kong over a 1-year programme. Each participant attended an individual oropharyngeal motor training programme plus a follow-up session after 2 months. The training programme consisted of 10 individual mobilization exercises involving the orofacial and pharyngeal area for 45 minutes. Each exercise had to be repeated for 10 times. Three outcome measures were chosen to study the effectiveness of the training programme including tongue strength, tongue endurance level and orofacial function. Tongue strength and tongue endurance level were assessed using the Iowa Oral Pressure Instrument (IOPI). The Nordic Orofacial Test-Screening (NOT-S) Assessment was used to assess the orofacial function. Seven out of 10 participants completed the training programme and attended the follow-up session after two months. Results: The tongue strength and the scores of NOT-S of the 7 participants were found to have significant improvement after training. However, there was no significant difference in tongue endurance level. Conclusion: The findings of this study support the role of occupational therapist in oromotor training modalities to improve the respiratory function for children with OSAS in Hong Kong.